The impact of neighborhood types on the prices of residential properties - Tan, Teck-Hong * (Sunway University College, 2010)
This paper attempts to examine the impact of neighborhood types on residential property prices in the Klang Valley, Malaysia. Results show that the gated-guarded landscape compound neighborhood could attract higher market prices by 14.26%, and the freehold neighborhood could fetch a 20.68% higher price than the leasehold neighborhood. It is interesting to note that house buyers are willing to pay 23.52% to live in the gated-guarded and freehold neighborhoods. In order to meet the increasingly demanding house buyers, instead of just offering dram houses in prime locations, housing developers should provide intangible benefits in the neighborhood that are just as sought after by today?s house buyers, such as a sense of security, a feeling of harmony with one?s surroundings, and an infrastructure which supports a eco-friendly lifestyle.